Study protocol: Audit and Best Practice for Chronic Disease Extension (ABCDE) Project - Thompson Sandra; Condon John; O'Donohue Lynette; Dowden Michelle; Clark Louise; Weeramanthri Tarun; Connors Christine; Si Damin; Bailie Ross; Clelland Nikki; Nagel Tricia; Gardner Karen; et al. (BMC, 2008)
Abstract Background A growing body of international literature points to the importance of a system approach to improve the quality of care in primary health care settings. Continuous Quality Improvement (CQI) concepts and techniques provide a theoretically coherent and practical way for primary care organisations to identify, address, and overcome the barriers to improvements. The Audit and Best Practice for Chronic Disease (ABCD) study, a CQI-based quality improvement project conducted in Australia's Northern Territory, has demonstrated significant improvements in primary care service systems, in the quality of clinical service delivery and in patient outcomes related to chronic illness care. The aims of the extension phase of this study are to examine factors that influence uptake and sustainability of this type of CQI activity in a variety of Indigenous primary health care organisations in Australia, and to assess the impact of collaborative CQI approaches on prevention and management of chronic illness and health outcomes in Indigenous communities. Methods/design The study will be conducted in 40-50 Indigenous community health centres from 4 States/Territories (Northern Territory, Western Australia, New South Wales and Queensland) over a five year period. The project will adopt a participatory, quality improvement approach that features annual cycles of: 1) organisational system assessment and audits of clinical records; 2) feedback to and interpretation of results with participating health centre staff; 3) action planning and goal setting by health centre staff to achieve system changes; and 4) implementation of strategies for change. System assessment will be carried out using a System Assessment Tool and in-depth interviews of key informants. Clinical audit tools include two essential tools that focus on diabetes care audit and preventive service audit, and several optional tools focusing on audits of hypertension, heart disease, renal disease, primary mental health care and health promotion. The project will be carried out in a form of collaborative characterised by a sequence of annual learning cycles with action periods for CQI activities between each learning cycle. Key outcome measures include uptake and integration of CQI activities into routine service activity, state of system development, delivery of evidence-based services, intermediate patient outcomes (e.g. blood pressure and glucose control), and health outcomes (complications, hospitalisations and mortality). Conclusion The ABCD Extension project will contribute directly to the evidence base on effectiveness of collaborative CQI approaches on prevention and management of chronic disease in Australia's Indigenous communities, and to inform the operational and policy environments that are required to incorporate CQI activities into routine practice.